ANALISIS MINIMUM IGNITION ENERGY (MIE) BAHAN BAKAR AVTUR (JET-A1) - Wibowo, Santosa Edy (Jurnal TEDC, 2026)
This research aims to analyze and document the Minimum Ignition Energy (MIE) of JET A-1 fuel. MIE, or the minimum energy required for ignition, is a crucial safety parameter in the handling and storage of aviation fuels. The methodology follows the ASTM E582 standard, measuring the electrical spark energy needed to ignite JET A-1 vapor under standard conditions (25°C and 1 atm). The study found that the MIE for JET A-1 fuel ranges from 0.2 mJ to 0.5 mJ at the optimum mixture ratio. This confirms that the fuel has a moderate to high ignition risk. The MIE value is significantly influenced by various factors, including temperature and pressure. At temperatures above its flash point (>38°C), the MIE decreases sharply, while dynamic conditions like vibration and sloshing can lower the fuel's flammability limits. A deep understanding of the MIE of JET A-1 is essential for mitigating fire and explosion risks. The findings emphasize the necessity of implementing strict safety measures, such as controlling spark sources, grounding equipment, and ensuring adequate ventilation, to enhance safety standards in the aviation industry.